Drosophila Tsc1 functions with Tsc2 to antagonize insulin signaling in regulating cell growth, cell proliferation, and organ size. - Potter, C.J.; Huang, H.; Xu, T. (Cell, 2001)
Tuberous sclerosis complex is a dominant disorder that leads to the development of benign tumors in multiple organs. We have isolated a mutation in the Drosophila homolog of TSC1 (Tsc1). Cells mutant for Tsc1 are dramatically increased in size yet differentiate normally. Organ size is also increased in tissues that contain a majority of mutant cells. Clones of Tsc1 mutant cells in the imaginal discs undergo additional divisions but retain normal ploidy. We also show that the Tsc1 protein binds to Drosophila Tsc2 in vitro. Overexpression of Tsc1 or Tsc2 alone in the wing and eye has no effect, but co-overexpression leads to a decrease in cell size, cell number, and organ size. Genetic epistasis data are consistent with a model that Tsc1 and Tsc2 function together in the insulin signaling pathway.